Nocturnal blood pressure non-dipping is not associated with increased left ventricular mass index in hypertensive children without end-stage renal failure - Seeman, Tomáš; Hradský, Ondřej; Gilík, Jiří (European journal of pediatrics, 2016)
UNLABELLED: The aim of our study was to investigate whether nocturnal blood pressure (BP) dip is associated with increased left ventricular mass index and hypertrophy in children with hypertension (HT). We retrospectively reviewed data from all children with confirmed ambulatory HT in our center and performed ambulatory blood pressure monitoring (ABPM) and echocardiography at the same time. Left ventricular hypertrophy (LVH) was defined as left ventricular mass index (LVMI) ≥95th centile. Non-dipping phenomenon was defined as nocturnal BP dip <10 %. A total of 114 ABPM studies were included, the median age of children was 15.3 years (3.8-18.9), 80 children had renoparenchymal HT without end-stage renal failure, 34 had primary HT, and 27 studies were done on untreated children and 87 on treated children. Non-dipping phenomenon was present in 63 (55 %) studies (non-dippers). The LVMI adjusted for age was not significantly different between non-dippers and dippers (0.87 ± 0.03 vs. 0.81 ± 0.02, p = 0.13). Left ventricular hypertrophy was not significantly higher in non-dippers than in dippers (20 vs. 9 %, p = 0.12). CONCLUSION: Hypertensive children without end-stage renal failure with non-dipping phenomenon do not have increased prevalence of LVH or higher LVMI adjusted for age than hypertensive children with preserved nocturnal BP dip. WHAT IS KNOWN: • Adult and pediatric hypertensive patients with end-stage renal failure have often nocturnal blood pressure non-dipping phenomenon. • Non-dipping phenomenon is in patients with end-stage renal failure associated with increased prevalence of left ventricular hypertrophy. What is New: • Pediatric hypertensive patients without end-stage renal failure with blood pressure non-dipping phenomenon do not have increased prevalence of left ventricular hypertrophy.
Keywords: hypertenze; Male; Statistics, Nonparametric; Non-dipping; retrospektivní studie; senzitivita a specificita; předškolní dítě; Children; antihypertenziva; neparametrická statistika; krevní tlak; Antihypertensive Agents; Child, Preschool; Humans; Nocturnal blood pressure dip; cirkadiánní rytmus; mužské pohlaví; Female; mladiství; chronické selhání ledvin; Blood Pressure; hypertrofie levé komory srdeční; ženské pohlaví; Retrospective Studies; echokardiografie; Hypertrophy, Left Ventricular; Left ventricular hypertrophy; Sensitivity and Specificity; Circadian Rhythm; Echocardiography; Adolescent; Hypertension; lidé; dítě; Blood Pressure Monitoring, Ambulatory; Kidney Failure, Chronic; Child; ambulantní monitorování krevního tlaku